Combined immunochemotherapy in patients with refractory/relapsed classical Hodgkin's lymphoma as a 2nd line treatment before autologous hematopoietic stem cell transplantation (preliminary results) - A. A. Mamedova; N. E. Mochkin; V. O. Sarzhevskiy; E. A. Demina; V. S. Bogatyrev; A. A. Spornik; A. A. Samoylova; A. A. Rukavitsin; E. G. Smirnova; A. E. Bannikova; V. Ya. Melnichenko; N. B. Mikhaylova; et al. (Онкогематология)
Aim. To study the efficacy and safety of combined immunochemotherapy according to the DHAp protocol + nivolumab in patients with refractory/relapsed classical Hodgkin's lymphoma before autologous hematopoietic stem cell transplantation.Materials and methods. The study consisted of 2 phases: 1st - immunotherapy with nivolumab (2 injections as monotherapy at a dose of 240 mg/day with 14 days interval); 2nd - combined immunochemotherapy according to the DHAp protocol + nivolumab (14 days after the 2nd administration of nivolumab): nivolumab 480 mg/day on day 1 in combination with chemotherapy according to the DHAp protocol, 4 cycles in total. The effectiveness of therapy was evaluated after 2 injections of nivolumab, after 2 and 4 cycles of combination therapy. from March 2020 to November 2021, 32 patients were included in the study. The median age was 34 (18-55) years.Results. As of November 2021, the result was evaluated in 32 patients after the 1st stage of treatment (nivolumab monotherapy). A complete response was obtained in 4 (12.5 %) patients, a partial response in 20 (62.5 %) patients, disease stabilization was noted in 5 (16 %) patients, an indeterminate response in 3 (9 %) patients. At the 2nd phase, the efficacy after the 2nd cycle of DHAp + nivolumab was evaluated in 31 patients (complete response was obtained in 19 (61 %), partial response in 11 (36 %)); the final efficacy evaluation (after the 4th cycle of DHAp + nivolumab) was performed in 30 patients, and all patients achieved response to therapy (complete response in 25 (83 %), partial response in 5 (17 %)). 2 patients were excluded from the study.Conclusion. preliminary results of combined immuno- and chemotherapy according to the DHAp protocol showed high efficacy and relatively low toxicity in patients with refractory/relapsed classical Hodgkin's lymphoma before autologous hematopoietic stem cell transplantation.